2006
DOI: 10.1093/ajcn/84.5.1193
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between fat distribution, muscle lipid content, adipocytokines, and insulin resistance: effect of moderate weight loss in older women

Abstract: Fat distribution indexes and adiponectin are independently associated with insulin resistance. Even in older women, moderate weight loss improves body fat distribution, muscle lipid infiltration, and insulin resistance. Moderate weight loss results in a significant decrease in leptin but no changes in adiponectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
90
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 38 publications
10
90
1
Order By: Relevance
“…In fact, for healthy human subjects and animal, moderate weight loss did not necessarily translate to changes in the plasma adiponectin level. 23,24 For subjects with metabolic abnormalities, weight loss larger than 10% was needed to change plasma adiponectin levels. 25 Also, patients with defective growth hormone receptor showed elevated plasma adiponectin despite marked obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, for healthy human subjects and animal, moderate weight loss did not necessarily translate to changes in the plasma adiponectin level. 23,24 For subjects with metabolic abnormalities, weight loss larger than 10% was needed to change plasma adiponectin levels. 25 Also, patients with defective growth hormone receptor showed elevated plasma adiponectin despite marked obesity.…”
Section: Introductionmentioning
confidence: 99%
“…only ADIPO was an independent BMD predictor in postmenopausal women and middle-aged men [47][48][49][50]. Other authors found that both LP and ADIPO were determinants of BMD; RES was negatively correlated with BMD, but the correlation did not reach statistical significance (p = 0.062) [51].…”
Section: Prace Oryginalnementioning
confidence: 93%
“…OC concentrations were also positively correlated with ADIPO [43][44][45][46]. OPG concentrations were higher in a premenopausal than in a postmenopausal population [47][48][49]. The OPG/RANKL ratio correlated negatively with LP and positively with ADIPO independent of age, BMI and the time elapsed from menopause [45].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers demonstrated a decrease [49] or increase [50][51][52] of VISF concentrations in obese subjects. According to some authors [43,[85][86][87][88][89][90], the association between LP, ADIPO, RES and VISF and obesity is lent support by changes in adipocytokine concentrations following weight reduction (diet or surgery) in individuals with moderate or severe obesity. Significant weight reduction in women with moderate or severe obesity, apparently resulting from dietary treatment, has been found to be associated with decreased LP and RES and increased ADIPO circulating concentrations [85][86][87].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…According to some authors [43,[85][86][87][88][89][90], the association between LP, ADIPO, RES and VISF and obesity is lent support by changes in adipocytokine concentrations following weight reduction (diet or surgery) in individuals with moderate or severe obesity. Significant weight reduction in women with moderate or severe obesity, apparently resulting from dietary treatment, has been found to be associated with decreased LP and RES and increased ADIPO circulating concentrations [85][86][87]. Weight loss after bariatric surgery in women and/or men with morbid obesity was associated with decreased LP, RES, VISF and increased ADIPO levels [43,[88][89][90].…”
Section: Prace Oryginalnementioning
confidence: 99%